2017
DOI: 10.1186/s41935-017-0034-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding of the Indian blackbuck (Antilope cervicapra) and their correlation with other closely related species

Abstract: Background: Sequence divergence in mitochondrial cytochrome c oxidase subunit I genes (COI) has been used as an efficient forensic tool in solving wildlife-related problems and also be used in molecular taxonomy for species identification. Methods: This study presents the DNA barcode sequences of the Blackbuck (Antilope cervicapra) from Haryana, India. A dataset of 43 partial COI sequences of 13 species belonging to 4 genus of Antilopinae sub-family were used for molecular analysis and to construct the phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…The overall sequence divergence patterns were consistent with many previous studies (Kumar et al 2017;Bhaskar et al 2020). Sequence divergence within each ungulate species was <1.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The overall sequence divergence patterns were consistent with many previous studies (Kumar et al 2017;Bhaskar et al 2020). Sequence divergence within each ungulate species was <1.…”
Section: Discussionsupporting
confidence: 90%
“…The advancement in species identification research using molecular techniques, particularly DNA barcoding has been a great milestone in determining ungulate diversity worldwide. It has been applied to studies regarding biodiversity, phylogeny, food adulteration cases, illegal trades of ungulates and their manufactured products (Kumar et al 2017;Zhong et al 2017;Khan et al 2018;Shukla et al 2019;Bhaskar et al 2020). However, most of the ungulate diversity of Pakistan has not yet been studied through mitogenome analysis and has been restricted to the pioneer morphological studies conducted by Schaller (1980), Mirza (1998), andRoberts (1997).…”
Section: Introductionmentioning
confidence: 99%
“…Results of the analysis of genetic distance between purebreed, CB cattle and B. taurus was in the range of 0.000 Genetic Diversity of Crossbred Cattle using Cytochrome Oxidase Subunit I (COI) Gene in South Sulawesi, Indonesia to 0.297. The result was in accordance with Kumar et al (2017b) who stated that the genetic diversity of COI gene in the Bovidae was between 0.0 and 1.92%. In this study showed that seven purebreed cattle might be grouped into B.taurus because it had a genetic distance of 0.000 (Angus, Brahman and Simmental), while Limousine has a genetic distance of 0.002 and Madura with a value of 0.013.…”
Section: Genetic Distance and Phylogenetic Tree Based On The Coi Genesupporting
confidence: 90%
“…Alternatively, for some specimens, a fragment with ~650 bp from the mitochondrial cytochrome c oxidase (coi) gene was amplified by two methods: (i) using the primers VF1_t1 (5 -TGT AAA ACG ACG GCC AGT TCT CAA CCA ACC ACA AAG ACA TTG G-3 ) [26] and VR1_t1 (5 -AGG AAA CAG CTA TGA CTA GAC TTC TGG GTG GCC AAA GAA TCA-3 ) [27] with PCR conditions and cycling from Kumar et al [28], and (ii) using the universal primers LCO 1490 and HCO 2198 [29] and PCR protocol based on Ruiz et al [30].…”
Section: Host Species Identificationmentioning
confidence: 99%